Faktor-Faktor yang Memengaruhi Pengambilan Keputusan Petani Bawang Putih dalam Menjalin Kemitraan (Studi Kasus di Desa Segorogunung, Kabupaten Karanganyar) - Herlinda Nur Fitriana; Eny Lestari; Suminah Suminah (AGRITEXTS: Journal of Agricultural Extension, 2022)
Garlic cultivation is one of the high-value farming development activities. One of the garlic-producing areas in Karanganyar Regency is Segorogunung Village. Farmers in Segorogunung Village in garlic farming have partnered with CV Berkat Putih Abadi and carried out the first harvest in 2019 after 20 years of vacuum. This study aims to (1) examine the decision-making of farmers in establishing partnerships; (2) analyzing the factors that influence farmers in establishing partnerships; (3) analyzing the factors that influence farmers' decision-making in establishing partnerships. The basic research method used is quantitative with survei techniques. The location selection was purposively in Segorogunung Village, Karanganyar Regency. A sampling of 66 respondent farmers was carried out using the proportional random sampling technique. Data analysis used logistic regression test with IBM Statistic 22 application. The results showed that: (1) age factors, farm area, income, formal education, non-formal education, economic environment, and social environment affect farmers' decisions in establishing partnerships; (2) factors in the form of age, non-formal education, economic environment, and social environment are included in the high category; income and formal education are in a low category, and the area of farming land is included in the very low category; (3) simultaneously the independent variables have a significant effect on the dependent variable, while partially the variables of age, economic environment, and social environment on farmer’s decisions, while the variables of farming land area, income, formal education, and non-formal education have no significant effect on farmers' decisions in establishing partnerships.